Controlled Capture of Magnetic Nanoparticles from Microfluidic Flows by Ferromagnetic Antidot and Dot Nanostructures - Reyne Dowling; Mikhail Kostylev (Nanomaterials)
The capture of magnetic nanoparticles (MNPs) is essential in the separation and detection of MNPs for applications such as magnetic biosensing. The sensitivity of magnetic biosensors inherently depends upon the distribution of captured MNPs within the sensing area. We previously demonstrated that the distribution of MNPs captured from evaporating droplets by ferromagnetic antidot nanostructures can be controlled via an external magnetic field. In this paper, we demonstrate the capture of magnetic nanoparticles from a microfluidic flow by four variants of antidot array nanostructures etched into 30 nm thick Permalloy films. The nanostructures were exposed to 130 nm MNP clusters passing through microfluidic channels with square cross-sections of 400 μm × 400 μm. In the presence of a parallel magnetic field, up to 83.1% of nanoparticles were captured inside the antidot holes. Significantly higher proportions of nanoparticles were captured within the antidots from the flow than when applying the nanoparticles via droplets. In the parallel field configuration, MNPs can be focused into the regularly spaced antidot indents in the nanostructure, which may be useful when detecting or observing MNPs and their conjugates. Conversely, up to 84% of MNPs were caught outside of antidots under a perpendicular magnetic field. Antidot nanostructures under this perpendicular configuration show potential for MNP filtration applications.